1992
DOI: 10.1007/bf00189623
|View full text |Cite
|
Sign up to set email alerts
|

Vascular changes in the ruptured achilles tendon and paratenon

Abstract: Thirty patients with ruptures of the Achilles tendon were studied. There were 21 men and 9 women with an average age of 36 years. Specimens from the tendon and paratenon in 24 were examined histologically. Tissue samples of 20 were studied by electron microscopy. Marked degenerative, obliterative and/or inflammatory vascular changes were found in all the ruptured tendons and their paratenon. Our findings indicate that poor vascularity play a role in the aetiology of rupture of the Achilles tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 22 publications
(25 reference statements)
0
25
0
4
Order By: Relevance
“…Thirty-five percent of the central tendon part's blood supply goes through the paratendon (12,13), which was dissected and compromised during tenotomy. The reason for this lies in the fact that at the muscle tendon junction capillaries and arterioles located between muscle fibers are entering between the secondary tendon fibers bundles (fascicules) and do not pass deeper than the first third of the tendon (14).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five percent of the central tendon part's blood supply goes through the paratendon (12,13), which was dissected and compromised during tenotomy. The reason for this lies in the fact that at the muscle tendon junction capillaries and arterioles located between muscle fibers are entering between the secondary tendon fibers bundles (fascicules) and do not pass deeper than the first third of the tendon (14).…”
Section: Discussionmentioning
confidence: 99%
“…4 Alternatively, there may be general collagen abnormality aVecting both disc and tendon, making them both prone to disruption in some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…2 3 Vascular alterations can play a role in the degenerative process preceding Achilles tendon rupture. 4 Previous studies have also shown that, in fresh samples of ruptured Achilles tendons, there is a pathological increase in the content of type III collagen. 5 Alterations in Achilles tendons and intervertebral disc biochemistry have also been hypothesised to be important in causing pathological changes eventually leading to rupture and prolapse respectively.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Most theories are based on mechanical and degenerative factors. Degeneration of tendon tissue is a consistent fi nding (Kvist et al 1992). When a tendon ruptures, various pre-existing degenerative changes may be found, including hypoxic degeneration, lipomatotis, mucoid degeneration, calcifi cation and occasionally necrosis.…”
Section: Etiology Of Achilles Tendon Rupturementioning
confidence: 99%